2019
DOI: 10.3390/ijerph16245152
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothesis and Evidence That Mercury May be an Etiological Factor in Alzheimer’s Disease

Abstract: Mercury is one of the most toxic elements and causes a multitude of health problems. It is ten times more toxic to neurons than lead. This study was created to determine if mercury could be causing Alzheimer’s disease (AD) by cross referencing the effects of mercury with 70 factors associated with AD. The results found that all these factors could be attributed to mercury. The hallmark changes in AD include plaques, beta amyloid protein, neurofibrillary tangles, phosphorylated tau protein, and memory loss—all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 72 publications
0
35
0
8
Order By: Relevance
“…These organic forms of mercury bio-accumulate in the food chain and thus people who consume highly contaminated seafood, including fish, shellfish, getsseverely affected [111]. The brain is a highly susceptible organ to methyl-mercury and sufficient evidences are linked with several vascular disorders including damage to BBB, vascular dementia, endothelial dysfunction, white matter hyperintense, and stroke [112][113][114][115]. Earlier studies concluded that multifactorial mechanisms have been suggested in Hg induced toxicity and oxidative stress is one of primary mechanism involved in the BBB permeability impairment, which modifies Hg induced neurotoxicity [40,116].…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…These organic forms of mercury bio-accumulate in the food chain and thus people who consume highly contaminated seafood, including fish, shellfish, getsseverely affected [111]. The brain is a highly susceptible organ to methyl-mercury and sufficient evidences are linked with several vascular disorders including damage to BBB, vascular dementia, endothelial dysfunction, white matter hyperintense, and stroke [112][113][114][115]. Earlier studies concluded that multifactorial mechanisms have been suggested in Hg induced toxicity and oxidative stress is one of primary mechanism involved in the BBB permeability impairment, which modifies Hg induced neurotoxicity [40,116].…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…Methylmercury (MeHg) is considered extremely neurotoxic to the developing brain and chronic exposure to this environmental neurotoxicant may be associated with increased risk of accelerated cognitive decline and neurodegenerative diseases. Indeed, mercury intoxication has been implicated in the etiology of Alzheimer's dementia (Siblerud et al, 2019), putatively causing profound and lasting cognitive decline with aging. Natural and anthropogenic-related environmental disasters may increase the exposure of human populations to mercury intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…The half-life of mercury is 30-60 days, while in the brain it reaches about 20 years. The binding of elemental mercury to the brain after oxidation is due to selenium, which probably contributes to the retention of mercury for a longer period of time ( 25 ).…”
Section: Toxic Environmental Factorsmentioning
confidence: 99%